2020
DOI: 10.3390/s20072073
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Brachial–Ankle Pulse Wave Velocity and Heart–Finger Pulse Wave Velocity in Korean Adults

Abstract: Arterial stiffness is considered an index of vascular aging. The brachial–ankle pulse wave velocity (baPWV) method is widely used because of its proven effectiveness; and the pulse wave velocity measurement method using both electrocardiogram (ECG) and photoplethysmogram (PPG) is actively being studied due to the convenience of measurement and the possibility of miniaturization. The aim of this study was to evaluate and compare the effects of age and gender in Korean adults using both the baPWV method and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…In this study, heart-finger PWV in a healthy subject was similar to the previous global PWV [ 30 ]. However, since this value was different from that of cerebral-artery PWV between CCA and ICA, appropriate attention is necessary when assessing vascular stiffness in cerebral-artery PWV using devices that measure global PWV.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, heart-finger PWV in a healthy subject was similar to the previous global PWV [ 30 ]. However, since this value was different from that of cerebral-artery PWV between CCA and ICA, appropriate attention is necessary when assessing vascular stiffness in cerebral-artery PWV using devices that measure global PWV.…”
Section: Discussionsupporting
confidence: 83%
“…Normal values for baPWV in different age groups vary according to the race and the country of the study was conducted. [ 39 , 40 ] Our study results showed a mean BaPWV of 1640.39 ± 309.20 cm/s. According to the 2013 National Physical Fitness project in Korea, 283 older adults showed baPWV in the age group 70 to 74 years of 1617.9 ± 244.4.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, PPG htPWV had only moderate overall agreement with the referent caPWV. Tsai et al ( 7 ) and Cho et al ( 8 ) conducted the only prior studies comparing PPG against criterions. Tsai et al ( 7 ) reported a moderate correlation ( r = 0.68, p < 0.01) between PPG finger-toe PWV and tonometric cfPWV as well as higher PWV values (from both devices) in subjects with hypertension and dyslipidemia, while Cho et al ( 8 ) showed a strong correlation in females ( r = 0.79, p < 0.01) but not males ( r = 0.34, p = 0.34), between PPG hfPWV and oscillometric brachial-ankle PWV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared PPG-based PWV assessments to traditional PWV techniques with mixed findings (i.e., r = 0.34-0.95) (7)(8)(9)(10)(11). The fact that these studies failed to consistently demonstrate strong relationships between PPG and criterion PWV techniques is likely partially attributed to the fact that these studies compared different arterial segments, and thus are not directly comparable.…”
Section: Introductionmentioning
confidence: 99%